Carbon Monoxide Is Involved in Hydrogen Gas-Induced Adventitious Root Development in Cucumber under Simulated Drought Stress - Chen, Yue; Wang, Meng; Hu, Linli; Liao, Weibiao; Dawuda, Mohammed M.; Li, Chunlan (Frontiers in Plant Science, 2017)
Hydrogen gas (H2) and carbon monoxide (CO) are involved in plant growth and developmental processes and may induce plant tolerance to several stresses. However, the independent roles and interaction effect of H2 and CO in adventitious root development under drought conditions have still not received the needed research attention. We hypothesize that there exists crosstalk between H2 and CO during adventitious root development under drought stress. The results of our current study revealed that 50% (v/v) hydrogen-rich water (HRW), 500 μM Hemin (the CO donor) and 30% (w/v) CO aqueous solution apparently promoted the development of adventitious roots in cucumber explants (Cucumis Sativus L.) under drought stress. H2 and CO increased relative water content, leaf chlorophyll content (chlorophyll a, b and a+b) and chlorophyll fluorescence parameters [photochemical efficiency of photosystem II (PSII), PSII actual photochemical efficiency and photochemical quench coefficient] under drought condition. When the CO scavenger hemoglobin (Hb) or zinc protoporphyrin IX (ZnPPIX) was added to HRW/CO aqueous solution, the positive effect of HRW/CO aqueous solution on relative water content, leaf chlorophyll content and chlorophyll fluorescence parameters were reversed. Additionally, superoxide dismutases, peroxidase, catalase and ascorbate peroxidase was significantly increased in the explants treated with HRW and CO aqueous solution under drought stress, thus alleviating oxidative damage, as indicated by decreases in thiobarbituric acid reactive substances (TBARS), hydrogen peroxide (H2O2) and superoxide radical (O2-) levels. H2 and CO also improved the levels of water soluble carbohydrate, total soluble protein and proline content. However, the above CO/H2-mediated effects were reversed by CO scavenger Hb or CO specific synthetic inhibitor ZnPPIX. Therefore, CO may be involved in H2-induced adventitious rooting under drought stress and alleviate oxidative damage by enhancing relative water content, leaf chlorophyll content, chlorophyll fluorescence parameters, metabolic constituent content, activating anti-oxidant enzymes and reducing TBARS, O2- and H2O2 levels.